Running a Smooth 4-H Business Meeting - Chris DeCubellis (EDIS)
A quality 4-H club meeting consists of three main parts: (1) the business meeting, (2) an educational component, and (3) a recreational component. This 4-page fact sheet focuses on running a smooth 4-H business meeting. Written by Chris DeCubellis and published by the UF Department of 4-H Youth Development, July 2014.